Comparative Study of Teacher Education Programs: Indonesia vs. Singapore - Evans Adam; Rina Kartika Sari (Mauve Journal De Leardu, 2025)
This study provides a comparative examination of teacher education programs in Indonesia and Singapore, focusing on their structures, policies, and practices that shape teacher preparation. Using a qualitative comparative approach, it analyzes policy documents, secondary data, and prior studies to understand how both countries develop their teaching workforce. Indonesia has implemented major reforms to improve teacher qualifications, promote continuous professional development, and reduce regional disparities, yet it still struggles with uneven implementation, limited resources, and weak quality assurance. Conversely, Singapore maintains a centralized and cohesive system under the National Institute of Education (NIE), integrating recruitment, training, and career progression with national education goals. Its program emphasizes selective entry, mentorship, and sustained professional learning, positioning teaching as a high-status profession. The analysis suggests Indonesia could adopt aspects of Singapore’s structured model especially in teacher preparation, professional development, and policy alignment while tailoring them to its socio-cultural and regional diversity. The study enriches discussions on teacher education reform and provides policy insights for improving the quality and equity of teacher training systems.